Transcriptomic analysis of the liver, jejunum, and uterus in different production stages of laying hens - Gi Ppeum Han; Byeonghwi Lim; Jun-Mo Kim; Deok Yun Kim; Hyun Woo Kim; Dong Yong Kil (Poultry Science, 2025)
Egg production in laying hens is related to very complex and elaborate processes involving the cooperation of various tissues. Laying hens undergo this complicated production process in different production stages during overall laying periods. However, many previous studies have focused on a single tissue or specific production stage. Thus, we compared multi-tissue transcriptome profiles across different production stages using RNA-seq to understand which overall metabolic changes occur in laying hens as the stage progresses. Laying hens at three distinct production stages of early-phase (EP, 30 wk of age), mid-phase (MP, 46 wk of age), and late-phase (LP, 60 wk of age) were used to analyze transcriptomic changes for the liver, jejunum, and uterus tissues. Weighted gene co-expression network analysis was adopted to detect core modules and central genes, and finally identified 11 co-expression modules. In the liver and jejunum, the expression of genes (e.g., FABP2, FABP7, PPARG) related to fatty acid synthesis was increased with production stages. However, the expression of genes (e.g., GSTA2, BLB1 and BLB2) related to immune responses, including xenobiotic metabolism pathway and the herpes simplex virus 1 infection pathway, was increased in EP compared with other stages. Moreover, the expression of genes related to calcium signaling pathways (e.g., CACNA2D1) and muscle contraction metabolism (e.g., ACTG2 and RYR2) in the uterus was decreased as laying hens were aged. The current findings pave the way for future investigations into the physiological changes in laying hens across different production stages. This research also provides a foundation for elucidating the multi-tissue transcriptome in laying hens and identifying potential genes regulating various biological processes during overall laying periods.